Preconception Evaluation Before In Vitro Fertilization. Issue 6 (June 2020) - Howell, Elizabeth P.; Harris, Benjamin S.; Kuller, Jeffrey A.; Acharya, Kelly S.
Abstract : Importance: Infertility poses a substantial public health problem for women of reproductive age, in the United States and globally. Infertility can be overcome with a variety of emerging assisted reproductive technologies (ARTs). In vitro fertilization (IVF) currently represents the most commonly utilized method of ART and is typically associated with the highest clinical pregnancy rate and live birth rate compared with other infertility treatment options. However, proper preconception evaluation and counseling is paramount for optimizing IVF and pregnancy outcomes. Objective: This article aims to outline current guidelines and recommendations for comprehensive preconception evaluation before initiation of IVF. Evidence Acquisition: Articles were obtained from PubMed, ACOG committee opinions 781 and 762, and relevant textbook chapters. Results: A variety of recommendations and best practices exist for optimally managing patients seeking IVF. Special attention must be paid to the workup of certain patient populations, such as those with age older than 35 years, uterine abnormalities, comorbidities (especially hypertension, diabetes, and thrombophilias), and obesity. In addition, many lifestyle factors must be addressed before IVF initiation, such as smoking, illicit drug use, and inadequate nutrition. Preconception counseling and expectation management is key to optimizing pregnancy outcome. Conclusions and Relevance: A myriad of patient and environmental factors impact the potential success rates of IVF in treating infertility. Providers must be equipped to provide data-driven, patient-centered counseling before initiation of IVF. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completion of this CME article, readers should be better able to explain the importance of IVF in treating infertility for a variety of patient populations; describe current recommendations and best practices for preconception workup and counseling; identify important risk factors and patient-specific comorbidities that warrant additional evaluation or attention before IVF treatment; and recommend patient-centered preconception counseling for their future patients seeking IVF.